Hypofractionated radiosurgery for meningiomas—a safer alternative for large tumors? - Smith, Damon E.; Ghosh, Sanjay; O’Leary, Michael; Chu, Colin; Brody, David (Translational Cancer Research, 2014)
Objective: To define the rate of tumor control and factors associated with relief of symptoms and radiationrelated complications after hypofractionated radiosurgery for patients with imaging defined intracranial meningiomas. Methods: Retrospective review of 30 tumors treated in 28 patients (22 women, 6 men) treated with hypofractionated radiosurgery for imaging-defined intracranial meningiomas between 2006 and 2012. The mean patient age was 60 years. The majority of tumors involved the skull base (n=15, 50%) and the convexity (n=8, 27%). The mean treatment volume was 14.7 cm3 (range, 0.79-64.5 cm3), fifteen of the tumors were greater than 9 cm3 in volume. Most patients were treated with a 5 fraction course of 4.5 to 6 Gy/fraction. The mean new conformality index was 1.61 (range, 1.2-2.28). Mean follow-up is 32.6 months, ranging from 12-66 months. Results: No patient died from tumor progression or radiation-related complications. There were no instances of in-field progression; one patient experienced marginal tumor progression outside the field (scalp nodules) which required surgical resection. The crude local control rate is 100%. Four patients experienced side effects as a result of their treatment. One patient with a parasagittal tumor experienced increasing hemiparesis as a result of increased peritumoral edema and required resection. One patient with a tumor near the orbital apex experienced diplopia which is persistent at 17 months. One patient with a skull based tumor in the infratemporal fossa, who had been treated with surgery and external beam radiation therapy prior to radiosurgery and who was treated to a very large volume (65 cm3), experienced cognitive changes and headaches requiring months-long steroid therapy. These symptoms have since resolved. One patient with a convexity lesion experienced headaches secondary to post-treatment edema which required a 3 months long course of steroid therapy. The rate of permanent morbidity is 3.5%. No patient died of tumor or treatmentrelated causes. Eight patients presented with symptoms ranging from headaches to visual changes; in 6 of these patients the symptoms were improved or resolved at the time of last follow-up. Conclusions: Hypofractionated radiosurgery with a dose of 22.5-30 Gy in five fractions appears to provide a high rate of tumor control and a low incidence of side effects for patients with imaging defined intracranial meningiomas, despite the large size (>9 cm3) of half of the tumors. Patients who were symptomatic at the time of presentation had a >66% chance of improvement or amelioration of their symptoms. Further longterm follow-up will be necessary to confirm efficacy.